2003
DOI: 10.1007/s102380300012
|View full text |Cite
|
Sign up to set email alerts
|

The clinical role of interleukin-6 and interleukin-6 soluble receptor in human follicular fluids

Abstract: In order to investigate the role of interleukin-6 (IL-6) and interleukin-6 soluble receptor (sR) in human ovulation, we evaluated the concentrations in human follicular fluid and analyzed the correlation of IL-6 and IL-6 sR with oocyte maturation. The oocytes were obtained from the follicular fluid of 45 women undergoing in vitro fertilization and embryo transfer. The concentrations of IL-6 and IL-6 sR in follicular fluid were measured by ELISA. In addition, granulosa cells obtained from the follicular fluid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 31 publications
(31 reference statements)
4
28
0
1
Order By: Relevance
“…FF levels of IL-6 were unrelated to COH protocol or fertilization rates and in this context our findings are consistent with published data [33,34]. Given our study design where FF samples were pooled for each patient, we cannot relate FF IL-6 with individual oocytes within each follicle; the linear relationship observed between FF IL-6 and yield of mature oocytes however, is supportive of previously published work by Kawasaki et al [25]; these authors described higher IL-6 levels in fluid from follicles yielding mature oocytes. Our data identify adverse influences of an intrafollicular inflammatory milieu on successful CP following fresh embryo transfer; given the lack of observed detriment on parameters of COH nor on fertilization, endometrial receptivity may be identified as a likely target for deleterious influences of elevated FF IL-6 levels, as suggested by the observed decline in rates of CP and implantation with increasing FF IL-6 levels.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…FF levels of IL-6 were unrelated to COH protocol or fertilization rates and in this context our findings are consistent with published data [33,34]. Given our study design where FF samples were pooled for each patient, we cannot relate FF IL-6 with individual oocytes within each follicle; the linear relationship observed between FF IL-6 and yield of mature oocytes however, is supportive of previously published work by Kawasaki et al [25]; these authors described higher IL-6 levels in fluid from follicles yielding mature oocytes. Our data identify adverse influences of an intrafollicular inflammatory milieu on successful CP following fresh embryo transfer; given the lack of observed detriment on parameters of COH nor on fertilization, endometrial receptivity may be identified as a likely target for deleterious influences of elevated FF IL-6 levels, as suggested by the observed decline in rates of CP and implantation with increasing FF IL-6 levels.…”
Section: Discussionsupporting
confidence: 94%
“…Measurements of serum and follicular fluid (FF) levels of IL-6 in women undergoing in vitro fertilization (IVF) have been shown previously to be associated with etiology of infertility, stimulation protocol, fertilization rates and pregnancy outcome [7,[23][24][25][26], and increased FF levels of IL-6 are described in the context of ovarian hyperstimulation syndrome [27].…”
Section: Introductionmentioning
confidence: 98%
“…In the present study, we investigated the changes in the expression of IL-6 receptors (IL-6Rα, IL-6sR and gp130) in granulosa cells and follicular fluid during atresia. The expressions of IL-6Rα and gp130 in human and rat granulosa cells [33,35] and IL-6sR in human follicular fluid [36] have previously been reported. We detected the expressions of IL-6Rα and gp130 in granulosa cells and IL-6sR in follicular fluid from the porcine ovary.…”
Section: Discussionmentioning
confidence: 85%
“…Presently, there is accumulating evidence suggesting that individual cytokines in human follicular fluid can be used as predictors of IVF outcome [30]. A positive association of IL-6 with oocyte maturation [31] and IL-1β with embryo development and pregnancy [32] is documented. A majority of findings have indicated that IL-12 is negatively associated with folliculogenesis, oocyte quality, and implantation [30,33,34].…”
Section: Discussionmentioning
confidence: 99%